Ticagrelor combined with aspirin may improve patency of vein graft one year after off-pump coronary artery bypass grafting: a single-center, randomized double-blinded clinical controlled trial - Wang, Wenjun; Chi, Qingzhuo; Gao, Feng; He, Xuezhi; Gao, Yang; Shi, Lei; Liu, Wei; Fan, Weiwang; Zhang, Lin; Xu, Chang; Zhuang, Xijing (Frontiers in Cardiovascular Medicine, 2025)
BackgroundDual anti-platelet therapy (DAPT) after coronary artery bypass graft surgery (CABG) has drawn a lot of controversy. This study aimed to explore the effects of ticagrelor combined with aspirin (compared with aspirin combined with clopidogrel) on the patency of saphenous vein graft (SVG) after off-pump CABG.MethodsThis was a prospective, randomized, double-blinded clinical controlled trial. Participants were first given aspirin (100 mg/d) within 12 h after off-pump CABG, followed by P2Y12 receptor antagonist (Orally, 75 mg/time of clopidogrel, once daily, for Group C and 90 mg/time of ticagrelor, twice daily, for Group T) within 24 h after off-pump CABG for one year. Computed tomography angiography (CTA) was conducted for all patients. The incidence of major adverse cardiac events(MACE), death, stroke, hemorrhage, left ventricular diameter (LVD), and left ventricular ejection fraction (LVEF) of the participants was assessed one year after off-pump CABG based on a 12-month follow-up.ResultsA total of 73 participants completed the follow-up, and 219 bypass grafts, including 146 SVGs, were conducted. Notably, 11 bypass grafts (SVGs) were exposed to occlusion (9 in Group C and 2 in Group T). The overall occlusion rates of bypass grafts and SVGs of Groups C and T were significantly different (9/114 vs. 2/105, P = 0.043, 9/76 vs. 2/70, P = 0.04). Moreover, multivariate binary Logistic regression demonstrated that ticagrelor + aspirin anti-platelet therapy could reduce the stenosis risk of bypass grafts (OR = 0.195, 95% CI = 0.039-0.978, P = 0.047).ConclusionsCompared with clopidogrel, ticagrelor may reduce the occlusion rate of vein grafts after CABG.Clinical Trial Registration[https://www.chictr.org/], identifier [ChiCTR1900022390].